By the way of the North American(s) Intervention(s): the OAS and the Multilateral Force - Torres Del Río, César (Pontificia Universidad Javeriana, 2014)
The study is the result of historical research. The methodological approach used was based on tha analysis of the evolution of the Inter-American (Multilateral) Peace Force. In this sense, the development of the Organizations of the American States (OAS) within the geopolitical strategic framework of the United States is analyzed, among others. We will attempt prove that the "new" proposition of the American Delegation at the XXXth OAS Assembly (Guatemala, june 1999) about an "Friends Countries Group" is interventionist and negative for the nationals soberanities.